Analisis Faktor-Faktor yang Berhubungan Dengan Higiene dan Sanitasi di Kantin Universitas Muhammadiyah Jakarta - Rusman Efendi; Andriyani Andriyani; Mustakim Mustakim (Jurnal Kesehatan Indonesia, 2018)
In Indonesia health environment is still one of health problem nowadays. According to study from Yunus et al 38.7% food handlers at The Padang restaurant in Manado and Bitung has not good criteria in personal hygiene, 35,4% place for food processing is not good, and 51.6% have unmet water supply requirement. This study aims to find know factors are related to hygiene and sanitation at University of Muhammadiyah Jakarta (UMJ) canteen. This study was observational study used a cross-sectional design to determine the relationship between knowledge, availability facilities and infrastructure of sanitation hygiene with hygiene and sanitation at cafeteria of the University of Muhammadiyah Jakarta. Subjects in this study were whole canteen and food handlers in UMJ. Study carried out in December 2016. The data were analyzed univariat and bivariate. The results of the study found that canteen with poor criteria in sanitation is 62.7%, and poor hygiene criteria is 60.8%. Variable that indicates a significant relationship are infrastructure, knowledge and education. But all variables showed no association with hygiene variable. Variable that shows no relation to sanitation is the duration of work.There is a significant relationship between infrastructure, knowledge and education to sanitation canteen, in the University of Muhammadiyah Jakarta.